Perioperative challenges and management strategies for non-cardiac surgery in patients with rheumatic heart diseases: A narrative review - Manila Singh; Abey Abraham; Swati Chhabra Soni; Saket Singh (Journal of Anaesthesiology Clinical Pharmacology)
Rheumatic heart diseases (RHDs) impose a substantial global burden, primarily affecting individuals under 25 years of age in low- and medium-income countries (LMICs) and poor and marginalized groups in high-income countries.[1-3] The underlying cause is a group A beta-hemolytic streptococcus, which triggers an immune-mediated attack on the heart and joints. Although acute rheumatic fever (ARF) is treatable, its occurrence and complications remain high in impoverished areas.[4] Variations in social structure contribute to differences in the incidence and progression of the disease, even in affluent regions.[5] Administering anesthesia to this patient population presents significant challenges, particularly when early management has been inadequate due to limited medical care and follow-up. Literature shows evidence for anesthetic management of different types of RHDs, mostly focusing on mitral and aortic valvulopathies.[6,7] This review synthesizes literature from databases such as MEDLINE and PubMed searches from the year 2000 to date, focusing on anesthesia management strategies and the challenges posed by ARF and RHD. Specific topics covered include the diagnosis and management of ARF, acute complications, perioperative care for patients with RHD, and unique considerations for different valvular pathologiesWith this review, we aim to discuss the available evidence, current World Health Organization (WHO) and societal guidelines in the context of perioperative medical and anesthetic management, hemodynamic challenges, and postoperative courses. An emphasis on basic point-of-care ultrasound (POCUS) training is made in this review as the current era of diagnostics and therapeutics is increasingly reliant on echocardiography.